Effects of Free and Nanoencapsulated Benznidazole in Acute Trypanosoma cruzi Infection: Role of Cholinergic Pathway and Redox Status - da Silva A.D. (2024)
© 2024 by the authors.Background/Objectives: The Trypanosoma cruzi infection promotes an intense inflammatory process that affects several tissues. The cholinergic system may exert a regulatory immune response and control the inflammatory process. This study aimed to evaluate the comparative effect of free and nanoencapsulated benznidazole in acute T. cruzi infection to assess hematological, biochemical, and oxidative status triggered by the cholinergic system. Methods: For this, fifty female Swiss mice were distributed in eight groups, i.e., uninfected and infected animals under four treatment protocols: untreated (control—CT); vehicle treatment (Eudragit L 100—EL-100); benznidazole treatment (BNZ); and nanoencapsulated benznidazole treatment (NBNZ). After eight treatment days, the animals were euthanized for sample collection. Results: The peak of parasitemia was at day 7 p.i., and the BNZ and NBNZ controlled and reduced the parasite rate but showed no efficacy in terms of total elimination of parasites analyzed by RT-PCR in both infected groups. The infection promotes significant anemia, leukopenia, and thrombocytopenia, which the BNZ improves. There was an increase in AChE activity during infection, leading to a pro-inflammatory response and an increase in M1 and M2 mACh receptors in the BNZ group, showing that the treatment interacted with the cholinergic pathway. In addition, a pro-oxidative response was characterized in the infection and mainly in the infected BNZ and NBNZ groups. The histopathological analysis showed significative splenomegaly and inflammatory infiltrate in the heart, liver, and spleen. Conclusions: The administration of the BNZ or NBNZ reverses hematological, hepatic, and renal alterations through cholinergic signaling and stimulates a pro-inflammatory response during acute T. cruzi infection.